Application of Foamed Concrete and Cold-Formed Steel Decking as Lightweight Composite Slabs: Experimental Study On Structural Behaviour - Jaini, Z. M.; M. Rum, R. H.; Seyed Hakim, S. J.; Mokhatar, S. N. (International Journal of Integrated Engineering, 2023)
Foamed concrete composite slabs (FCCS) are currently enjoying great popularity in the construction industry. Unlike conventional composite slabs, FCCS has an advantage in solving the selfweight penalty. With the advanced research in concrete technology, foamed concrete with sufficient strength properties  to meet the requirements of standard code of practise has been successfully introduced. Foamed concrete is known for its lightweight and versatility. This paper presents an experimental study on ultimate load, maximum deflection and failure mode of FCCS. Of interest are the effects of dry density and slab thickness. The slab specimens with a span of 1800 mm, a width of 840 mm and different thicknesses from 100 mm to 150 mm were prepared for the three-point bending test. The dry density of foamed concrete is 1400 kg/m3, 1600 kg/m3, and 1800 kg/m3, which has a compressive strength of about 20 MPa to 40 MPa. Dry density and slab thickness have been observed to have significant effects on ultimate load and maximum deflection. Higher dry density of foamed concrete provides better slip resistance and thus reduces shear bond failure. On the other hand, slab specimens with a higher slab thickness tend to have better bearing capacity due to greater bending stiffness. The main failure mode is dominated by localised bending on the profiled steel deck, slip-displacement and fracture of the foamed concrete.